2020
DOI: 10.3390/foods9060704
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Limited Amounts of Extruded Legumes Plus Cereal Mixes in Normocaloric or Obesogenic Diets for Rats: Effects on Lipid Profile

Abstract: Overweight and obesity are regarded as world epidemics and are major risk factors for a number of chronic diseases, including diabetes, cardiovascular diseases, and cancer. Two new highly palatable extruded mixes based on rice and pea (Pisum sativum) or kidney bean (Phaseolus vulgaris) meals were incorporated into normocaloric or obesogenic diets for rats at a low inclusion level (25%). Our purpose was to evaluate the effects of dietary incorporation of this new food ingredient on lipid profile. Organs (heart,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…For results on growth and feed intake, organs and visceral fat relative weights, bile acids in feces, liver and plasma cholesterol and triglycerides, and long-chain fatty acid composition of liver and visceral fat, see the accompanying paper. 34 RT-qPCR analysis of microbiota profile in intestinal contents and feces Data on small intestinal (ileum) bacteria log 10 copy numbers after consumption of the experimental diets are collected in Table 3. Obesogenic diets did not affect bacterial counts, while the inclusion of the extruded mixes gave place to significantly lower (P < 0.005) values in the counts of most of the bacterial groups studied (bifidobacteria, Blautia coccoides / Eubacterium rectale, Clostridium leptum / Ruminococcus spp, enterobacteria and Escherichia / Shigella).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For results on growth and feed intake, organs and visceral fat relative weights, bile acids in feces, liver and plasma cholesterol and triglycerides, and long-chain fatty acid composition of liver and visceral fat, see the accompanying paper. 34 RT-qPCR analysis of microbiota profile in intestinal contents and feces Data on small intestinal (ileum) bacteria log 10 copy numbers after consumption of the experimental diets are collected in Table 3. Obesogenic diets did not affect bacterial counts, while the inclusion of the extruded mixes gave place to significantly lower (P < 0.005) values in the counts of most of the bacterial groups studied (bifidobacteria, Blautia coccoides / Eubacterium rectale, Clostridium leptum / Ruminococcus spp, enterobacteria and Escherichia / Shigella).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, an extract of pea albumins led to an anti-inflammatory effect at the colon level in mice, accompanied by a modulation in the composition of the intestinal microbiota, [30][31] and dark kidney beans or cranberry bean supplements suppressed colonic inflammation and reduced the severity of DSS-induced colitis in mice. [32][33] As explained in the accompanying paper, 34 new highly palatable extruded mixes of legumes plus cereals similar to a snack food have been produced 35 and incorporated in limited amounts into normocaloric or obesogenic diets for rats. Our purpose was to evaluate the effects of dietary incorporation of this new food ingredient on lipids (accompanying paper 34 ) and intestinal microbiota composition (current paper).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methionine restriction attenuated insulin resistance triggered by HFD and restored the periodic fluctuation of lipidolysis genes and bile acid synthetic genes interrupted by HFD, thus improving the circulating lipid profile (Wang et al, 2020). A recent study revealed that new food ingredient-extruded legumes plus cereal mixes can modulate lipid profiles and increase fecal excretion of bile acids (Rubio et al, 2020). This research drives our attention to the nutritional and physiological effects of extruded legumes plus cereal mixes.…”
Section: Effect Of Dietary Intervention On the Composition Of The Gutmentioning
confidence: 99%
“…Hamsters on the black bean diet tended to have higher bile acid excretion. Additionally, working with inclusion of limited amounts of extruded legumes plus cereal mixes in normocaloric or obesogenic diets for rats, Rubio et al (2020) found a lowering (p < 0.05) excretion of cholic, chenodeoxycholic and ursodeoxycholic acids and deoxycholic acid and total bile acids higher (p < 0.01) for rats fed extruded mixes compared with controls.…”
Section: Plasma Lipoprotein Profilementioning
confidence: 99%